2012
DOI: 10.1371/journal.pone.0042866
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the FDA's AERS Database Regarding Muscle and Tendon Adverse Events Linked to the Statin Drug Class

Abstract: BackgroundCholesterol management drugs known as statins are widely used and often well tolerated; however, a variety of muscle-related side effects can arise. These adverse events (AEs) can have serious impact, and form a significant barrier to therapy adherence. Surveillance of post-marketing AEs is of vital importance to understand real-world AEs and reporting differences between individual statin drugs. We conducted a review of post-approval muscle and tendon AE reports in association with statin use, to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 44 publications
0
90
2
3
Order By: Relevance
“…The use of the other statins is considered either moderate or low‐intensity statin therapy 1. Hoffman et al reported the following order for the relative risk of statin‐induced MAEs: rosuvastatin > atorvastatin > simvastatin > pravastatin > lovastatin 25. These indicate that the higher the HMG‐CoA reductase inhibitory activity (or the lower the IC 50 ) of a statin, the higher the relative risk of MAEs tends to be.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the other statins is considered either moderate or low‐intensity statin therapy 1. Hoffman et al reported the following order for the relative risk of statin‐induced MAEs: rosuvastatin > atorvastatin > simvastatin > pravastatin > lovastatin 25. These indicate that the higher the HMG‐CoA reductase inhibitory activity (or the lower the IC 50 ) of a statin, the higher the relative risk of MAEs tends to be.…”
Section: Discussionmentioning
confidence: 99%
“…Higher potency therapy is associated with an increased rate of adverse effects, particularly myalgias, which may hinder compliance. 23,24 We found that patients receiving therapy of lower potency than when on their branded statin were also significantly less compliant with therapy compared to patients receiving equipotent doses. Although these findings are seemingly contradictory, patients who experienced adverse events and required dose decreases at the time of switching may have been less inclined to continue on statin therapy, even at lower doses.…”
Section: Discussionmentioning
confidence: 85%
“…[11][12][13][14] It is one of the primary tools used for post-marketing surveillance and pharmacovigilance, because it is the largest, most well-known database worldwide, and it reflects the realities of clinical practice.…”
Section: Analysis Of the Interaction Betweenmentioning
confidence: 99%